East-West paths to unconventional computing. (December 2017) - Adamatzky, Andrew; Akl, Selim; Burgin, Mark; Calude, Cristian S.; Costa, José Félix; Dehshibi, Mohammad Mahdi; Gunji, Yukio-Pegio; Konkoli, Zoran; MacLennan, Bruce; Marchal, Bruno; Margenstern, Maurice; Martínez, Genaro J.; et al.
Abstract: Unconventional computing is about breaking boundaries in thinking, acting and computing. Typical topics of this non-typical field include, but are not limited to physics of computation, non-classical logics, new complexity measures, novel hardware, mechanical, chemical and quantum computing. Unconventional computing encourages a new style of thinking while practical applications are obtained from uncovering and exploiting principles and mechanisms of information processing in and functional properties of, physical, chemical and living systems; in particular, efficient algorithms are developed, (almost) optimal architectures are designed and working prototypes of future computing devices are manufactured. This article includes idiosyncratic accounts of 'unconventional computing' scientists reflecting on their personal experiences, what attracted them to the field, their inspirations and discoveries.